BIMBINGAN KEPRIBADIAN DALAM PEMENUHAN HAK PENDIDIKAN BAGI NARAPIDANA SEBAGAI UPAYA PENINGKATAN INTELEKTUAL - Mutiara Sari, Agnes Roulina; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Prisoners' educational rights are regulated in Law number 22 of 2022 concerning corrections. Prisoners who participate in the Strata-1 (S1) education program are expected to experience an increase in intellectual intelligence. The methodology used in this research is a qualitative method using a descriptive approach research design to explain the observations made. The data sources in this research use primary data and secondary data. The informants in this research consisted of 3 prisoners who had completed a strata-1 (S1) education program. Research data collection was carried out by field research and literature research. The results of this research are that prisoners who are included in the strata-1 (S1) education program experience intellectual improvement as seen from 3 (three) indicators of intellectual intelligence, namely verbal intelligence, practical intelligence and numerical intelligence. In this research, researchers carried out updates in personality guidance in fulfilling educational rights for prisoners as an effort to improve intellectually Keywords: Educational Rights; Prisoners; Intellectual Intelligence